COMPARITIVE BIODEGRADATION OF SYNTHETIC POLYMERS (LDPE, HIPS AND NYLON 6) USING PLEUROTUS OSTREATUS - ARUN KUMAR. J; GOPINATH. L; APRAJEETHA. J; DECCARAMAN. M; SHANTHA PREMA RAJ (International Journal of Pharma and Bio Sciences, 2015)
In the present study degradative ability of Pleurotus ostreatus was tested against LDPE, NYLON 6 and HIPS. Growth and enzyme activity were optimized to attain maximum degradability with parameters like pH, temperature and initial carbon source. Enumeration of degradation with loss of weight was further analysed by FTIR spectroscopy and SEM analysis. It has been observed based on results that Pleurotus ostreatus degrades Nylon 6 by much higher level (45.7%) followed by LDPE (36.9%) and HIPS (27%) in optimised MSM medium with lignin as initial carbon source. Changes in functional groups and surface degradation were observed in NYLON 6.